Fatal hepatic necrosis after isoflurane anaesthesia - Weitz, Jürgen; Kienle, Peter; Böhrer, Hubert; Hofmann, Walter J.; Theilmann, Lorenz; Otto, Gerd (Anaesthesia, 1997)
Several halogenated anaesthetic agents have been associated with hepatotoxicity. We report a case of fulminant, fatal hepatic necrosis after uneventful isoflurane anaesthesia in a patient without previous liver disease, who may have been sensitised by previous exposure to enflurane. Although no anti-trifluoroacetyl antibodies could be detected in the patient's serum, isoflurane hepatotoxicity seems very likely to be the reason for fulminant hepatic failure in this patient.